Islamic Legal Epistemology As The Foundation Of Business Ethics In Sharia-Based Creative Economy - Ahmad Fahrur Rido; Anwar Ma'rufi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The growth of the sharia-based creative economy in the digital era presents complex ethical challenges, particularly concerning the commercialization of values, digital plagiarism, and cultural exploitation. The urgency of this research lies in the effort to construct a business ethics paradigm rooted in the epistemology of Islamic law that is not merely normative, but also rational and contextual. The primary objective of this study is to examine how the epistemology of Islamic law can function as a foundation for shaping business ethics within a sharia-based creative economy. This research adopts a qualitative approach with a normative–philosophical orientation, employing a literature review of classical sources such as uṣūl al-fiqh texts, as well as contemporary works in Islamic economics and business ethics. The analytical techniques used include content analysis, hermeneutics, and conceptual analysis. The findings indicate that the epistemology of Islamic law generates a value system that balances economic creativity with moral responsibility through the principles of maqāṣid al-sharīʿah, justice, trust (amānah), and public welfare (maṣlaḥah). The proposed model of sharia-based creative business ethics emphasizes that Islamic law functions not only as a formal regulatory framework but also as a system of value production that shapes ethical awareness in economic innovation. This study recommends further empirical research to strengthen the application of sharia principles within the digital creative economy ecosystem.